Multiple myeloma: routes to diagnosis, clinical characteristics and survival – findings from a UK population‐based study. (1st February 2017) - Howell, Debra; Smith, Alexandra; Appleton, Simon; Bagguley, Timothy; Macleod, Una; Cook, Gordon; Patmore, Russell; Roman, Eve
Summary: Prompt cancer diagnosis may align UK survival with European averages. We examined the impact of route to diagnosis on survival for multiple myeloma patients diagnosed 2012–2013 using data from our population‐based patient cohort that links to national death notifications and collects details on treatment and response ( n = 441). Emergency presentation was associated with advanced disease and poorer outcomes, and was the commonest route to diagnosis (28·1%) followed by General Practitioner urgent (19·0%) and two‐week wait (17·2%) referrals. CRAB (elevatedC alcium, R enal failure, A naemia, B one lesions) distribution varied by route ( P < 0·001), with patients with emergency presentations most likely to have ≥2 features and significantly worse survival (log‐rank test χ 2 = 13·8, P = 0·0002).